Gambaran Kebiasaan Mouth Breathing pada Anak Gangguan Spektrum Autisme (GSA) di Yayasan Biruku Kota Bandung - Meisya Alifah Praviani; Inne Suherna Sasmita (Universitas Muhammadiyah Manado, 2026)
Mouth breathing is a clinical condition characterized by mixed or additional breathing through the mouth that replaces the nasal breathing pattern. It is caused by mechanical factors such as septal deviation and adenotonsillar hyperplasia, inflammatory diseases such as allergic rhinitis, and habits. The purpose of this research is to determine the description of mouth breathing habits in GSA children at the Biruku Foundation, Bandung. This research was performed using descriptive method. The subjects were 15 autism spectrum disorder (ASD) collected by total sampling. The research was conducted by the mirror test examination. The results showed that 5 children have the mouth breathing habit (33%). Based on gender, 2 female children have the mouth breathing habit (50%) and 3 male children who have the mouth breathing habit (27.27%). This research shows that the percentage of mouth breathing habits in ASD children at the Biruku Foundation, Bandung, is quite high, with girls having a higher prevalence than boys.